Uso del método de Schour y Massler en la determinación de edad dental y cronológica a partir de radiografías panorámicas. - Tapia Viteri, Daniela Esthefanía (2023)
ABSTRACT: Achieving a successful dental treatment requires an accurate prior diagnostic of the patient´s oral cavity by analyzing several elements involved, like dental development, which can be evaluated using different dental age estimation methods. This study was conducted to determine the relationship between dental age and chronological age. The sample was 52 panoramic radiographs using the Schour and Massler method. This research is a descriptive, observational, quantifiable investigation using an observation sheet to record the variables. By performing the Kolmogorov- Smirnov test, it was shown that these data do not come from a normal distribution. Therefore they might be analyzed through a non-parametric test, such as the Wilcoxon range test, to contrast the information obtained and to determine if these data are within the expected parameters established by Schour and Massler method. Participants in this study were classified as 5, 6, 7, 8, 9, 10, 11, and 12 years. When applying the method, Schour and Massler obtained an arithmetic mean of 5,22; 6,0; 7,5; 8,1; 9,2; 10,3; 11,0; 12,1, respectively. Therefore, it is determined that this method can be applied for estimating dental age in panoramic radiographs, and it is recommended to carry out new studies that allow us to identify the method that best matches the Ecuadorian population for clinical and forensic purposes